ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN BANDA ACEH CITY - Fitria, Nurul; Linda, Linda; Fuadi, Raida; Febriyanti, Maya (Media Riset Akuntansi, Auditing & Informasi, 2025)
Village fund management is both a responsibility and a challenge for village officials in ensuring proper allocation and utilization. The use of these funds must be transparent and accountable to both the government and the community to prevent mismanagement. This study aims to evaluate the village fund accountability by examining the influence of supervision, human resource competence, and community participation. The research surveyed 132 respondents, comprising village heads, secretaries, and finance officers from 44 villages in Banda Aceh. Multiple linear regression analysis was employed. The findings reveal that supervision and community participation positively affect the village fund accountability, whereas the competence of village officials has no significant effect.